Coupling Molecular Spin Qubits with 2D Magnets for Coherent Magnon Manipulation - Dey, Sourav; Rivero-Carracedo, Gonzalo; Shumilin, Andrei; Gonzalez-Ballestero, Carlos; Baldoví, José J. (Nano letters, 2025)
Magnonics is an emerging field widely considered as a paradigm shift in information technology that uses spin waves for data storage, processing, and transmission. However, the coherent control of spin waves in 2D magnets still remains a challenge. Herein, we investigate the interplay between molecular spins and magnons in hybrid heterostructures formed by titanocene bis(cyclooctatetraenyl) [CpTi(cot)] and vanadyl phthalocyanine (VOPc) spin qubits deposited on the surface of the air-stable 2D van der Waals ferromagnet CrSBr using first principles. Our results show that different molecular rotation configurations significantly impact on qubit relaxation time and alter the magnon spectra of the underlying 2D magnet, allowing the chemical coherent control of spin waves in this material. We predict the feasibility of an ultrafast magnon-qubit interface with minimized decoherence, where exchange coupling plays a crucial role. This work opens new avenues for hybrid quantum magnonics, enabling selective tailoring through a versatile chemical approach.